Chercheurs étrangers et internationalisation du système scientifique au Mexique - Sylvie Didou (Cahiers de la Recherche sur l'Education et les Savoirs)
The question of foreign born researchers in Mexico is not an important topic on the national research agenda, despite its increasing importance as a factor in explaining the dynamics of in situ internationalization of the scientific system. After studying the public policies designed to attract them in the country, we present the results of 116 interviews. These deal with the process of their recruitment, career structures and collaboration networks. The information gathered enabled us to analyze the effects of the programs devoted to them and their strategies as specific actors in the national academic profession.